2009
DOI: 10.1016/j.yhbeh.2008.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Progesterone reduces the effect of the serotonin 1B/1D receptor antagonist, GR 127935, on lordosis behavior

Abstract: Ovariectomized rats were hormonally primed with 10 μg estradiol benzoate or with estradiol benzoate plus 500 μg progesterone. Rats received a bilateral infusion with 200 ng of the 5-HT 1B/1D receptor antagonist, N-[4-methoxy-3-(4-methyl-1-piperazinyl)phenyl]-2′-methyl-4′-(5-methyl-1,2,4-oxadiazol-3-yl)-1-1′-biphenyl-4-carboxamide hydrochloride (GR 127935), into the ventromedial nucleus of the hypothalamus (VMN), followed by a 5 min restraint or home cage experience. In estrogen-primed females that had experien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 65 publications
(87 reference statements)
1
16
0
Order By: Relevance
“…Instead of further confirming the importance of the 5-HT 1A receptor, we tried to block the paroxetine effects on female rat sexual behaviors with the 5-HT 1B antagonist GR125,743. The rationale for that was that 5-HT 1B agonists inhibit lordosis in female rats (Uphouse et al 2009), particularly when endogenous 5-HT release is heightened by stress . A heightened 5-HT release is exactly what is associated with SSRI treatment, and we reasoned that antagonism of the 5-HT 1B receptor might enhance female sexual behaviors after a paroxetine-induced reduction.…”
Section: Discussionmentioning
confidence: 99%
“…Instead of further confirming the importance of the 5-HT 1A receptor, we tried to block the paroxetine effects on female rat sexual behaviors with the 5-HT 1B antagonist GR125,743. The rationale for that was that 5-HT 1B agonists inhibit lordosis in female rats (Uphouse et al 2009), particularly when endogenous 5-HT release is heightened by stress . A heightened 5-HT release is exactly what is associated with SSRI treatment, and we reasoned that antagonism of the 5-HT 1B receptor might enhance female sexual behaviors after a paroxetine-induced reduction.…”
Section: Discussionmentioning
confidence: 99%
“…MBH infusion with the 5-HT 1B/1D receptor antagonist, GR 127935 N-[4-methoxy-3-(4-methyl-1-piperazinyl)phenyl]-2′-methyl-4′-(5-methyl-1,2,4-oxadiazol-3--yl)-1,1′-biphenyl-4-carboxamide hydrochloride (Liao et al, 2000), inhibited lordosis behavior in rats made sexually receptive with estradiol benzoate priming but was considerably less evident in rats hormonally primed with estradiol benzoate and progesterone (Uphouse et al, 2009). Interestingly, the effect of the 5-HT 1B/1D receptor antagonist appeared to result from an amplification of infusion stress on lordosis behavior (Uphouse et al, 2009).…”
Section: 0 Drugs Acting At 5-ht Receptorsmentioning
confidence: 99%
“…Interestingly, the effect of the 5-HT 1B/1D receptor antagonist appeared to result from an amplification of infusion stress on lordosis behavior (Uphouse et al, 2009). After infusion with the 5-HT 1B/1D receptor agonist, CP 93129 [1,4-dihydro-3-(1,2,3,6-tetrahydro-4- 27 pyridinyl)-5H-pyrrol[3,2-bi]pyridin-5-one-dihydrochloride] (Uphouse et al, 2010), rats primed only with estradiol benzoate showed lordosis inhibition, but in contrast to a transient decline in lordosis behavior following infusion with the antagonist, effects of CP 93129 were long lasting.…”
Section: 0 Drugs Acting At 5-ht Receptorsmentioning
confidence: 99%
“…In early studies with nonselective 5-HT 1B receptor compounds, a facilitative role for 5-HT 1B receptors was suggested (Aiello-Zaldivar et al, 1992; Mendelson and Gorzalka, 1990). In support of this possibility, infusion of a selective 5-HT 1B receptor antagonist, GR 127935, into the VMN amplified the negative effects of 5 min restraint on lordosis behavior of estradiol benzoate-primed ovariectomized rats (Uphouse et al, 2009). …”
Section: Introductionmentioning
confidence: 96%
“…Fischer rats have been reported to show evidence of high emotionality in a variety of behavioral tests (Dhabhar et al, 1993; Izumi et al, 1996; Rosecrans et al, 1986; Stohr et al, 2000) and show a larger hypothalamic-pituitary-adrenal response to stress than several other rat strains (Armario et al, 1995; Dhabhar et al, 1995; Gomez-Serrano et al, 2009; Marissal-Arvy et al, 2007; Rosecrans et al, 1986; Sarrieau and Mormede, 1998). Lordosis behavior of estradiol benzoate-primed Fischer females is also vulnerable to disruption by a mild stress (Truitt et al, 2003; Uphouse et al, 2009; White and Uphouse, 2004). In prior experiments, we have shown that a stressor as mild as 5 min of restraint can substantially reduce lordosis behavior of EO Fischer rats while having no effect in EP rats (Truitt et al, 2003).…”
Section: Introductionmentioning
confidence: 99%